2021
DOI: 10.2495/cmem-v9-n3-226-238
|View full text |Cite
|
Sign up to set email alerts
|

Phantom -based lumbar spine experimental investigation and validation of a multibody model

Abstract: The study of the biomechanics of the human spine is not yet developed extensively. Recent developments in this field have heightened the need for observing the spine from a comprehensive perspective to understand the complex biomechanical patterns, which underlie the kinematic and dynamic responses of this multiple-joint column. Within this frame of exigence, a joint study embracing experimental tests and multibody modelling was designed. This study provides novel insights to the segmental contribution profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The biomechanical loads applied to the biomimetic phantom included flexion, extension, and lateral bending as well as clockwise and anticlockwise axial rotation. Tests were performed recurring to a spine-loading apparatus already described in a previous study (Borrelli et al, 2021) and shown in Figure 1. Briefly, this spineloading apparatus orients the phantom to make the L3 inferior endplate horizontal, consistent with the anatomical orientation of lumbar segment (Wilke et al, 1998), and it allows bending through an eccentric vertical load applied to the cranial vertebra Frontiers in Bioengineering and Biotechnology frontiersin.org with S1 fixed to the machine (Patwardhan et al, 1999;Cripton et al, 2000;Marras et al, 2021;Ou et al, 2021;Garavelli et al, 2022).…”
Section: Testing Apparatus and Testing Proceduresmentioning
confidence: 99%
“…The biomechanical loads applied to the biomimetic phantom included flexion, extension, and lateral bending as well as clockwise and anticlockwise axial rotation. Tests were performed recurring to a spine-loading apparatus already described in a previous study (Borrelli et al, 2021) and shown in Figure 1. Briefly, this spineloading apparatus orients the phantom to make the L3 inferior endplate horizontal, consistent with the anatomical orientation of lumbar segment (Wilke et al, 1998), and it allows bending through an eccentric vertical load applied to the cranial vertebra Frontiers in Bioengineering and Biotechnology frontiersin.org with S1 fixed to the machine (Patwardhan et al, 1999;Cripton et al, 2000;Marras et al, 2021;Ou et al, 2021;Garavelli et al, 2022).…”
Section: Testing Apparatus and Testing Proceduresmentioning
confidence: 99%
“…The direction of this load can be either always vertical (M + LL1), or can maintain the same relative orientation with the most cranial vertebra during the motion (M + LL2), or can be defined so that the force acts along the line connecting the cranial vertebra’s center to the caudal vertebra’s center (M + LL3). Configurations M + LL1 and M + LL2 are actually equivalent to vertical eccentric forces generating both a bending moment and a compression force 6 , 19 . Rarely bending moments were obtained by applying a shear force along the construct’s antero-posterior direction 9 .…”
Section: Synthetic View Of Loading Set-ups In Literaturementioning
confidence: 99%
“… Study Spinal levels (No. of samples) Cranial vertebrae DOF Load Preload Classification Belwadi et al (2008) [ 3 ] T12–L2 (10), L4–S1 (9) Sagittal motion Force up to spinal failure HLsf, M Bennett et al (2013) [ 4 ] L4–L5 (6) Free 8 Nm FL 400 N M, M + LL2 Bennett et al (2015) [ 5 ] L4–-L5 (6) Free 8 Nm FL 400 N M, M + LL1, M + LL2 Borrelli et al (2021) [ 6 ] T12–S1 (1)—synthethic Free 3 Nm (F); 2 Nm (E) LL 1 N M + LL1 Charriere et al (2006) [ 7 ] L5–S1 (7) Free/Sagittal motion 2.5, 5, 7.5, 10 Nm M Cripton et al (2000) [ 8 ] L1–L2 (1), L2–L3 (3), L3–L4 (1), L4–L5 (1) Free/Sagittal motion 5 Nm LL 200, 400 N M, M + LL1, M + LL2 Demetropoulos et al (1998) [ 9 ] T12–L5 (10) Free Cranial vertebra motion HLsf Di Angelo et al ...…”
Section: Synthetic View Of Loading Set-ups In Literaturementioning
confidence: 99%
“…It is particularly suitable for biomechanical applications compared to other strain measurement techniques such as strain gauges, which are invasive and only provide a local measurement, or thermoelastic analyses, which in some conditions are not applicable to biological tissues [33,34]. Furthermore, optical measurements can be successfully coupled with finite element method and multibody modeling in order to achieve a complete mechanical characterization [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%